The Effect of Corporate Social Responsibility on Firm Value During COVID-19 - Josua Tarigan; Devina Nathania Joviaal; Albert Valentine (Universitas Pasundan, 2024)
This study reviews the relationship between corporate social responsibility (CSR), firm size, and the leverage on firm value. Panel data analysis is performed to test the sample in basic industries and the chemical sector over the years 2017-2020. To investigate any significant differences between CSR and firm value prior to the COVID-19 pandemic (years 2016–2019) and during the pandemic (years 2020), the authors performed paired sample t-testing. The results imply that the beneficial relevance of CSR performance could assist businesses in protecting their value at the start of a financial catastrophe, such as the COVID-19 pandemic. Therefore, during the COVID-19 era, businesses must continue to invest in CSR initiatives to maintain stakeholders' trust. This research advances previous CSR studies by offering further clarification on the conflicting results currently available about the influence of CSR on firm value during the COVID-19 period. Further research is necessary to determine whether the effects of CSR during the second year of the COVID-19 period differ from those during the pre-crisis period and the first year of the COVID-19 period.